2018
DOI: 10.1128/jvi.00280-18
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Domains Mediate Intra- and Extracellular Trafficking of Epstein-Barr Virus Latent Membrane Protein 1

Abstract: EBV latent membrane protein 1 (LMP1) is released from latently infected tumor cells in small membrane-enclosed extracellular vesicles (EVs). Accumulating evidence suggests that LMP1 is a major driver of EV content and functions. LMP1-modified EVs have been shown to influence recipient cell growth, migration, differentiation, and regulation of immune cell function. Despite the significance of LMP1-modified exosomes, very little is known about how this viral protein enters or manipulates the host EV pathway. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 82 publications
1
26
0
Order By: Relevance
“…Rab13 has pleiotropic roles, including the regulation of glucose transporter 4 trafficking [101], macrophage phagocytosis [102, 103], autophagy [104], lymphocyte trafficking [105], anoikis and metastasis [106–108]. Notably, LMP1 traffics to intracellular membranes to initiate signaling or to be secreted in exosomes [75, 94, 95, 109–112], though the chaperone protein(s) required for intracellular sorting are incompletely defined. Our results suggest that EBV co-opts Rab13 for yet another function: to chaperone oncogenic LMP1 and LMP2A to appropriate sub-cellular compartments where they can then activate downstream pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Rab13 has pleiotropic roles, including the regulation of glucose transporter 4 trafficking [101], macrophage phagocytosis [102, 103], autophagy [104], lymphocyte trafficking [105], anoikis and metastasis [106–108]. Notably, LMP1 traffics to intracellular membranes to initiate signaling or to be secreted in exosomes [75, 94, 95, 109–112], though the chaperone protein(s) required for intracellular sorting are incompletely defined. Our results suggest that EBV co-opts Rab13 for yet another function: to chaperone oncogenic LMP1 and LMP2A to appropriate sub-cellular compartments where they can then activate downstream pathways.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, EVs may also transfer virus-encoded proteins and nucleic acids independently of the viral particles. For instance, both simian immunodeficiency virus (SIV) ( McNamara et al, 2018 ) and HIV-1 ( Lenassi et al, 2010 ; Pereira and daSilva, 2016 ; Puzar Dominkus et al, 2017 ) induce the release of Nef protein in exosomes; EBV LMP1 is also secreted in EVs ( Meckes et al, 2010 ; Nkosi et al, 2018 ) and functional exosomes containing miRNAs have been detected in human clinical samples and mouse models of KSHV-associated malignancies ( Chugh et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…An ideal purification method would retain EV functional properties [ 60 , 61 ]. In the case of LMP1 modified EVs, we have previously shown that expression of this viral oncoprotein enhances the release of smaller EVs in different cell lines with an enrichment of different exosomal markers [ 49 , 50 ]. In this study, the EVs used were isolated by a combination of tangential flow filtration (TFF, 100kDa cutoff) followed by precipitation using PEG-6000 then ultracentrifugation to remove PEG and contaminating protein complexes ( Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have reported the significant role of EVs play in cell growth, invasion, and metastasis of diverse cancers [ 46 , 47 ]. EBV infected cells release EVs that can contain the viral proteins, LMP1 and LMP2, and virally encoded miRNAs [ 42 , 48 – 50 ]. EBV has been demonstrated to modify protein content and cargo of EVs released from latently infected B-cells with most of the significant changes correlating to LMP1 expression [ 51 ].…”
Section: Introductionmentioning
confidence: 99%